Agronomic, Physiological, Genetic and Phytochemical Characteristics of Onion Varieties Influenced by Daylength Requirements - Zahra Kiani; Kambiz Mashayekhi; Nadezhda Golubkina; Seyyed Javad Mousavizadeh; Khalil Zaynali Nezhad; Gianluca Caruso (Agriculture, 2023)
The evaluation of A. cepa biodiversity provides onion breeders with great prospects to obtain plants with high resistance to environmental factors, remarkable yield, and product quality. Genetic diversity assessment of a collection of nine short- and long-day onion landraces and varieties originated from different Iranian regions, using ISSR markers and UPGMA dendrograms, was carried out for the first time. Short-day landraces (Sarze, Sarkoreh, and Kerman) originated from low latitude and short-day hybrids (Mirela and Soberana) demonstrated high genetic similarity, in terms of physiological responses to day length and temperature during the crop cycle and bulbing stage initiation. Contrarily, high latitude landraces (Azarshahr, White Gorgan, Kurdistan, and Esfahan) showed low biometrical, agronomic and genetic similarity with commercial short-day onions. Specific differences in morphological reactions between these two groups displayed diverse responses of plants to day length and temperature. Long- and short-day cultivars displayed significant differences in the dynamics of leaf and scale number, leaf and root length, dry and fresh weight, and bulbing ratio and bulb diameter, which were in accordance with ISSR data. The local landraces Azarshahr, Kurdistan, and Esfahan had high antioxidant status, suggesting high prospects for their utilization as an alternative to foreign F1 hybrid varieties.